2011
DOI: 10.1371/journal.pone.0023914
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Wnt/β-Catenin Signaling Pathway by Mechanical Ventilation Is Associated with Ventilator-Induced Pulmonary Fibrosis in Healthy Lungs

Abstract: BackgroundMechanical ventilation (MV) with high tidal volumes (VT) can cause or aggravate lung damage, so-called ventilator induced lung injury (VILI). The relationship between specific mechanical events in the lung and the cellular responses that result in VILI remains incomplete. Since activation of Wnt/β-catenin signaling has been suggested to be central to mechanisms of lung healing and fibrosis, we hypothesized that the Wnt/β-catenin signaling plays a role during VILI.Methodology/Principal FindingsProspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 42 publications
1
62
0
Order By: Relevance
“…3 Recent studies using alveolar type II epithelial cells and rats have demonstrated that cyclic mechanical stretch can lead to disorganization and ECM remodeling of the lung by activating the Wnt/b-catenin pathway and inducing EMT. 6,7 In the current mouse model of VILI, we demonstrated that mechanical ventilation of bleomycintreated lungs of mice increased lung fibrogenesis, lung edema, microvascular permeability, fibroblast accumulation, epithelial apoptosis, hypoxemia, and PAI-1 and TGF-b1 production. Upregulation of Src is associated with increased lung injury.…”
Section: Discussionmentioning
confidence: 90%
“…3 Recent studies using alveolar type II epithelial cells and rats have demonstrated that cyclic mechanical stretch can lead to disorganization and ECM remodeling of the lung by activating the Wnt/b-catenin pathway and inducing EMT. 6,7 In the current mouse model of VILI, we demonstrated that mechanical ventilation of bleomycintreated lungs of mice increased lung fibrogenesis, lung edema, microvascular permeability, fibroblast accumulation, epithelial apoptosis, hypoxemia, and PAI-1 and TGF-b1 production. Upregulation of Src is associated with increased lung injury.…”
Section: Discussionmentioning
confidence: 90%
“…Cyclin D1 is a cell cycle regulatory molecule that is active in G1 phase transition and functions as an important mitogenic regulator (26). Increased cyclin D1 expression is linked to acute and chronic lung injuries induced by inflammatory agents, and it is postulated to contribute to interstitial cell proliferation and fibrosis formation (27,28). Collagen 1a1 and fibronectin are the main components of ECM that participate in tissue and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…A study of an acid-induced lung injury model in mice revealed that the 2-hour mechanical stretch induced lung fibrosis formation (Cabrera-Benitez et al 2012). Another study demonstrated that pulmonary fibrotic changes were induced at the early stage by mechanical ventilation in lungs without preexistent lung disease (Villar et al 2011). …”
Section: Discussionmentioning
confidence: 99%